2012
DOI: 10.3389/fgene.2012.00003
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of the DNA Repair Genes mutM, mutY, mutL, and mutS is Related to Proteome Size in Bacterial Genomes

Abstract: DNA repair is expected to be a modulator of underlying mutation rates, however the major factors affecting the distribution of DNA repair pathways have not been determined. The Proteomic Constraint theory proposes that mutation rates are inversely proportional to the amount of heredity information contained in a genome, which is effectively the proteome. Thus, organisms with larger proteomes are expected to possess more efficient DNA repair. We show that an important factor influencing the presence or absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…This observation suggests that the G:C/A:T balance of the genomes of different organisms might be determined, at least in part, by the functioning of their MMR system. In a recent survey of 699 bacterial genomes, about 20% lacked one or more genes in the MMR pathway, but there was no correlation with the G:C content of the genomes (48). Two caveats apply to these results: (i) other repair activities in the cell may compensate for the absence of MMR; and (ii), the presence of the MMR genes does not mean that the system is functioning to the same extent in each organism.…”
Section: Discussionmentioning
confidence: 88%
“…This observation suggests that the G:C/A:T balance of the genomes of different organisms might be determined, at least in part, by the functioning of their MMR system. In a recent survey of 699 bacterial genomes, about 20% lacked one or more genes in the MMR pathway, but there was no correlation with the G:C content of the genomes (48). Two caveats apply to these results: (i) other repair activities in the cell may compensate for the absence of MMR; and (ii), the presence of the MMR genes does not mean that the system is functioning to the same extent in each organism.…”
Section: Discussionmentioning
confidence: 88%
“…The long-lived GH-resistant GH receptor (GHR)-KO mice which have high GH level, as well as Ames dwarf and Snell dwarf mice lacking GHexhibit dwarfism, increased subcutaneous adiposity, change in tissue sizes, and increased insulin sensitivity[1, 20]. Although hNAG-1 mice are significantly shorter in body length (Figure 2a) there are no significant differences in tissue sizes, length of femurs or organ weights (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that hNAG-1 expression increases metabolic oxidation and thermogenesis in male mice which is responsible, in part, for the resistance of hNAG-1 mice to obesity [14]. Enhanced O 2 consumption and higher heat expenditure are consistent with increased oxidative metabolism and is associated with protection from HFD-induced obesity and enhanced longevity [1, 23]. In this study, heat production is slightly but statistically significant lower during the day in female line 1398 hNAG-1 mice (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations